Moving on a comparative case study of the mobile website adaptations of the Philippine Daily Inquirer and the Philippine Star - Albao, Myk Gregory L.; Miclat, Luis Miguel S.M.; Arao, Danilo P.; University of the Philippines. College of Mass Communication (2014)
"With the cheapening of smart devices and increasing internet accessibility, mobile media is slowly being acknowledged no loner as the "future" but as the "now" of journalism. News organizations can now provide news faster and at a much wider scale in this emerging medium. However, this shift to the mobile media is relatively news in the country, hence the researchers' focus on it, specifically how the top producers of news are adapting to it. This study aims to determine the effects and impact of mobile media to two of the country's top Philippine broadsheets, the Philippine Daily Inquirer and the Philippine Star, by studying how they are adapting to it specifically through their mobile websites, m.inquirer.net and m.philstar.com, respectively. Medium Theory was used as the theoretical lens and a variation of it as the main conceptual lens. Key informant and in depth interviews with PDi and PhilStar's mobile news heads, new media experts from the academic community, and an IT expert and manager at Globe were conducted over a period of two months. A comparative criteria analysis was also done by the researchers to have a closer look at and a more technical study of the two companies' mobile websites. The researchers found out both PhilStar and PDI's mobile websites were created only to respond to the growth of mobile internet users, repurposing articles from the desktop website and print to the mobile website for content. While PDI has a better mobile website than PhilStar, both companies are yet to maximize mobile media's potential and keep up with international standards."
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman
Keywords: News Web sites -- Philippines